Testing of weak form efficiency on selected shariah index in Bursa Malaysia / W Nurfara Anum W Mhd Kamal - W Mhd Kamal, W Nurfara Anum (Faculty of Business and Management, 2018)
The purpose of this study is to investigate the existence of Efficient Market Hypothesis (EMH) on selected Shariah Index in Bursa Malaysia. However, this study is only testing the weak form of EMH. The index chosen for this research is EMAS, HIJRAH, and MIDS CAP Index. The data was collected in for each index for daily basis from year 2013 to 2017. This study used Autoregressive Model to regress the past stock price with the current stock price. Tests employed for this study includes descriptive analysis, test for estimated empirical model, stationary tests and diagnostic tests. Result of this study reveals that for daily data, all the index has significant relationship which can be concluded as inefficiently weak. These results provide understanding towards investors, analysts and regulator in dealing with Efficient Market Hypotheses.